Early S-phase cell hypersensitivity to heat stress - Petrova, Nadezhda V. (Cell Cycle, 2015)
Heat stress is one of the best-studied exogenous stress factors; however little is known about its delayed effects. Recently, we have shown that heat stress induces cellular senescence-like G2 arrest exclusively in early S-phase cells. The mechanism of this arrest includes the generation of heat stress-induced single-stranded DNA breaks, the collision of replication forks with these breaks and the formation of difficult-to-repair double-stranded DNA breaks. However, the early S phase-specific effects of heat stress are not limited to the induction of single-stranded DNA breaks. Here, we report that HS induces partial DNA re-replication and centrosome amplification. We suggest that HS-induced alterations in the expression levels of the genes encoding the replication licensing factors are the primary source of such perturbations. Notably, these processes do not contribute to acquisition of a senescence-like phenotype, although they do elicit postponed effects. Specifically, we found that the HeLa cells can escape from the heat stress-induced cellular senescence-like G2 arrest, and the mitosis they enter is multipolar due to the amplified centrosomes.